KEANEKARAGAMAN, PERSEBARAN DAN POLA TATA RUANG TUMBUHAN EPIFIT PADA HUTAN BEKAS TEBANGAN DI KIYU, PEGUNUNGAN MERATUS, KALIMANTAN SELATAN [Diversity, Distribution and Spatial Patterns of Epiphytic Plants at The Logged Over Forest in Kiyu Forest, Meratus Mountain, South Kalimantan] - Sadili, Asep; Royyani, Mohammad Fathi (Research Center for Biology-Indonesian Institute of Sciences, 2018)
A quantitative study of epiphytic plants was conducted at the logged over forest in Kiyu, Meratus Mountain, Hulu Sungai Tengah, SouthÂ Kalimantan. This study used a plot of 10 m x 500 m (Â± 0,5 ha), and divided into 50 subplot of 10 m x 10 m. The results showed that thereÂ were nine species of six genera from three families of epiphytic plants found within the studied plot, with A grostophyllum bicuspidatum asÂ the dominant species. The diversity index (Hâ) was of 1,85. The diversity of epiphytic plant in these plots was well represented based on theÂ results of analysis of species area curve. Spatial distribution pattern of all epiphytic species was homogeneus, except forÂ A. bicuspidatum. The number of epiphytic host plants observed was 22 individuals from six species of six genera, and five families, withÂ Saurauia nudiflora (Acthiniaceae) was the dominant host plant.